2014
DOI: 10.7840/kics.2014.39c.11.1078
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Mobility Management Scheme for the Tactical Network

Abstract: In the conventional centralized mobility management schemes, it can lead to single points of failure, occurrence of a bottleneck, since all data and control are concentrated on the mobility anchor which is located in home network. In the current research of distributed mobility management, it is doing research into distributed mobility management which is supported by distributed mobility anchors. Such schemes do not consider a failure of the mobility anchor. However, it could be an issue under tactical enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This subsection describes some published studies on mobility management for tactical networks. Kim et al [22] proposed a DMM scheme for tactical networks. Their method aims to provide a handover even in the event of an anchor failure.…”
Section: Tactical Mobility Management Methodsmentioning
confidence: 99%
“…This subsection describes some published studies on mobility management for tactical networks. Kim et al [22] proposed a DMM scheme for tactical networks. Their method aims to provide a handover even in the event of an anchor failure.…”
Section: Tactical Mobility Management Methodsmentioning
confidence: 99%
“…For the performance analysis issue, Shin et al [12] analyzed the simulation data which showed DMM mechanism is more suitable for sensitive delay and tolerance than Proxy MIPv6. Giust et al [13] and Kim et al [14][15] showed signal control and data transmission cost analysis. However, those performances are all cost-based analyses, which are short of the comprehensive and systematic study.…”
Section: Introductionmentioning
confidence: 99%